A critical review of current methods in earthworm ecology: From individuals to populations - Bartlett, M.D.; Briones, M.J.I.; Neilson, R.; Schmidt, O.; Spurgeon, D.; Creamer, R.E.
Earthworms play an important role in the functioning of many terrestrial ecosystems, and while their importance is frequently acknowledged significant challenges still remain in determining their operant roles within the soil. This lack of knowledge becomes increasingly important as the spatial scale of analysis increases from individuals to populations within the landscape. To effectively develop understanding, research techniques must be able to determine the effects that earthworms have on the soil system, as well as to establish how many and which species are present. A range of techniques are required to facilitate meaningful analysis from the micro-scale within a soil profile (e.g. rilosphere effects)to a field scale or landscape scale. Furthermore, an additional framework of understanding is required to investigate the role of earthworms in the biogeochemical cycles. By critically evaluating recent advances in methods and data analysis techniques in three areas of earthworm research we highlight that combinations of common approaches often offer the most significant insights into the functional roles of earthworms within a soil system. Through particular reference to earthworm sampling and identification, biochemical functions and persistent pollutant ecotoxicology of temperate ecosystems we emphasise how a range of investigation methods can be a hindrance to developing a whole-system level understanding. The complex and diverse nature of soil systems means that a traditional compartmentalised approach studying single species using a single research technique is no longer sufficient to gain further insights into the earthworm contribution to ecosystemgoods and services delivered at the whole landscape scale. The integration of technologically advanced methods in combination with systems based modelling will be critical to develop landscape scale understanding of the functions of earthworms as individuals and as populations within in their ecosystems
Keywords: EARTHWORMS; LUMBRICIDAE; SAMPLING; MOLECULAR TECHNIQUES; STABLE ISOTOPES; ECOTOXICOLOGY; BIOGEOCHEMICAL CYCLING